2015
DOI: 10.3109/10428194.2014.966707
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms inTNFandIFNGare associated with clinical characteristics of aplastic anemia in Argentinean population

Abstract: The impaired hematopoiesis in acquired aplastic anemia (AA) results from immune-mediated mechanisms. We characterized polymorphisms implicated in controlling type-1 cytokine production in 69 patients with AA. Our data suggest that the studied polymorphisms are not associated with susceptibility in the overall AA population. However, the presence of the higher expressing TNF - 308A allele was associated with younger age (p = 0.0297) and more profound neutropenia (p = 0.0312), and over-represented in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
2
6
1
Order By: Relevance
“…No association was recorded in both the inflammatory cytokines after IST between AA and with those of control. Our results are in disagreement with previous reports that showed an association after IST [23,24].…”
Section: Discussioncontrasting
confidence: 99%
“…No association was recorded in both the inflammatory cytokines after IST between AA and with those of control. Our results are in disagreement with previous reports that showed an association after IST [23,24].…”
Section: Discussioncontrasting
confidence: 99%
“…Espinoza et al [94] reported that Antimoesin antibodies derived from AA patients can stimulate monocytic cells to secrete TNF-a through the activation of the ERK1/2 pathway provoked by direct binding to moesin. A recent study suggests that the high level TNF-a variants in AA patients is associated with clinical features, disease severity and therapy outcomes [95].…”
Section: Five-year Viewmentioning
confidence: 99%
“…Indirectly, IFNG acts on IFNG receptor‐expressing macrophages and stromal cells, that in turn may affect stem cell quiescence and exert a pull towards producing progenitor cells (Smith et al , ). A polymorphic site in the IFNG gene may increase susceptibility to developing AA, as well as its severity (Bestach et al , ), and may influence response to IST (Zeng et al , ). AA develops in mice genetically modified to express constitutively low levels of IFNG (Lin et al , ).…”
Section: The Effectors Of Damagementioning
confidence: 99%